2020
DOI: 10.4049/jimmunol.2000803
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tunneling Nanotube–like Structures during the Early Events of HIV Infection: Novel Features of Tissue Compartmentalization and Mechanism of HIV Spread

Abstract: HIV has become a chronic disease despite the effective use of antiretroviral therapy (ART). However, the mechanisms of tissue colonization, viral evolution, generation of viral reservoirs, and compartmentalization are still a matter of debate due to the challenges involved in examining early events of infection at the cellular and molecular level. Thus, there is still an urgent need to explore these areas to develop effective HIV cure strategies. In this study, we describe the early events of tissue colonizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 91 publications
1
40
0
Order By: Relevance
“…Several groups, including ours, have demonstrated that TNT formation is induced under several pathogenic conditions, including carcinogenesis 3 , 4 , 9 , 13 , 23 , 47 – 49 . In contrast, healthy adult cells express low to undetectable TNT levels 3 , 21 .…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Several groups, including ours, have demonstrated that TNT formation is induced under several pathogenic conditions, including carcinogenesis 3 , 4 , 9 , 13 , 23 , 47 – 49 . In contrast, healthy adult cells express low to undetectable TNT levels 3 , 21 .…”
Section: Resultsmentioning
confidence: 84%
“…Normally, TNT formation and associated intercellular communication participate in key biological processes, including development, signaling, and the immune response, but TNT formation during healthy conditions is minimal 1 8 . We and others demonstrated that TNT formation participates in the pathogenesis of several diseases, including HIV 9 13 . However, the role of TNT or tumor microtubes in glioblastoma (GBM) have only recently been explored 14 23 .…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations